PENGEMBANGAN MEDIA KARTU BERGAMBAR BERBASIS APLIKASI CANVA PADA MATERI PERISTIWA PROKLAMASI KEMERDEKAAN KELAS V DI SDN 1 BONO TULUNGAGUNG - Nur Hidayah nur; Ria Fajrin Rizqy Ana (Universitas PGRI Adi Buana Surabaya, 2023)
The development of learning media for fifth grade students at SDN 1 Bono Tulungagung is still lacking, this has an impact on activeness in learning. This problem is caused by the lack of availability of learning media in schools. students just sit, listen quietly, and take notes on what the teacher says. This study aims to develop, test the validity, and applicability of Canva application-based picture card media. This study uses the ADDIE development model which consists of analysis, design, development, implementation, and evaluation stages. Data collection techniques were carried out by testing the validity of the media, materials, and distributing questionnaires. The instruments used in this study used media expert validation sheets, material expert validation sheets, and student response questionnaire sheets to the media. The results of media validation by validator I obtained a percentage of 88.72% in the very good category, the media assessment by validator II obtained a percentage of 79.97% in the good category, the results of material validation by the validator obtained a percentage of 96.1% in the very good category, and the results the student questionnaire obtained a percentage of 89.73% in the very good category. The conclusion of this study is that Canva application-based picture card media is valid and suitable for use as learning media in elementary schools.